2002
DOI: 10.1046/j.1365-2893.2002.00365.x
|View full text |Cite
|
Sign up to set email alerts
|

A single nucleotide polymorphism of the low molecular mass polypeptide 7 gene influences the interferon response in patients with chronic hepatitis C

Abstract: Transporter associated with antigen processing (TAP) and low molecular mass polypeptides (LMP) play crucial roles in the human leukocyte antigen (HLA) class I-restricted antigen presenting systems. This study was performed to elucidate whether these antigen-presenting gene polymorphisms could influence the response to interferon (IFN) treatment in patients with chronic hepatitis C. Polymorphisms of TAP and LMP genes in 175 hepatitis C virus (HCV) patients were determined by polymerase chain reaction-restrictio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
37
0

Year Published

2003
2003
2013
2013

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 49 publications
(41 citation statements)
references
References 47 publications
4
37
0
Order By: Relevance
“…Few studies have investigated variations in other gene loci in relation to outcome of the antiviral therapy for chronic HCV infection, including cytokine genes, 36 -40 the mannose-binding lectin gene, 41 the gene for interferoninducible MxA protein, 42 the low molecular mass polypeptide 7 gene, 43 and the low-density lipoprotein receptor. 44 However, all of these studies had less than 80% power to detect moderate effects of gene variants because of a sample size of less than 100 individuals per subgroup.…”
Section: Discussionmentioning
confidence: 99%
“…Few studies have investigated variations in other gene loci in relation to outcome of the antiviral therapy for chronic HCV infection, including cytokine genes, 36 -40 the mannose-binding lectin gene, 41 the gene for interferoninducible MxA protein, 42 the low molecular mass polypeptide 7 gene, 43 and the low-density lipoprotein receptor. 44 However, all of these studies had less than 80% power to detect moderate effects of gene variants because of a sample size of less than 100 individuals per subgroup.…”
Section: Discussionmentioning
confidence: 99%
“…42,43 Fewer functional studies have been performed on LMP polymorphisms; however, it has been reported that the LMP2 R60H and LMP7 Q49K polymorphisms (in this report) affect age-dependent TNF-a apoptosis and response to interferon in patients with chronic hepatitis C, respectively. 44,45 Immunoproteasomes might also play an integral role in maintaining peripheral tolerance. Immunoproteasomes are constitutively expressed in the thymus and by mature dendritic cells under conditions in which most T-cell activation occurs, whereas elsewhere in the periphery constitutive proteasomes are expressed in the absence of inflammation.…”
Section: Discussionmentioning
confidence: 99%
“…Polymorphisms in several genes including MxA, PKR, OAS, 11 HLA, KIR, TNF, 12 and MICA have been shown to be associated with HCV clearance or persistence. 13,14 Studies have indicated that single nucleotide polymorphisms (SNPs) in the IL10, CTLA, MxA, and LMP7 genes may influence the response to IFN-a treatment in patients with chronic HCV [15][16][17] along with variants in the HLA. 13,14 The strength of the immune response may influence HCV-mediated fibrogenesis 10 through cytokines that stimulate extracellular matrix deposition such as TNF.…”
Section: Introductionmentioning
confidence: 99%